The ethical considerations for emergency care research in low- and middle-income countries: A scoping review of the published literature - Sarah Hirner; Colleen Saunders; Willem Stassen (African Journal of Emergency Medicine, 2022)
Introduction: Research studies on emergency care in low- and middle-income countries (LMICs) face many ethical considerations, including obtaining valid informed consent from vulnerable patients. This study aims to describe the body of literature related to the ethical considerations associated with emergency care research in low- and middle-income settings. Methods: A scoping review was conducted to identify literature published between 2000 and 2020 related to ethical considerations associated with emergency care research in the LMIC setting. Titles and abstracts were screened in duplicate, and full texts were reviewed and extracted by the principal author. Results: In total, 1087 articles were identified and 17 articles were included. Major themes identified in the literature included risk versus benefit assessments, patient vulnerabilities, consent, community engagement, clinical roles, ancillary care provision, and regulation of research. Alternative models of consent are often used in emergency care research, including surrogate consent, community consent, and waiver of consent. Challenges and best practices with these alternative models of consent in LMICs are discussed. Discussion: Gaps remain in the literature describing the ethics of emergency care research in LMICs, including clear guidelines for protecting vulnerable patients and designing ethical consent processes. Best practices identified include community engagement for designing research studies, identifying acceptable risk profiles, and allocating benefits. Continuous and rigorous assessment of the quality of consent is also needed.